Studies in Phase Space Analysis with Applications to PDEs - Cicognani, Massimo; Colombini, Ferruccio; Del Santo, Daniele (Progress in Nonlinear Differential Equations and Their Applications,, 2013)
This collection of original articles and surveys, emerging from a 2011 conference in Bertinoro, Italy, addresses recent advances in linear and nonlinear aspects of the theory of partial differential equations (PDEs). Phase space analysis methods, also known as microlocal analysis, have continued to yield striking results over the past years and are now one of the main tools of investigation of PDEs. Their role in many applications to physics, including quantum and spectral theory, is equally important. Key topics addressed in this volume include: *general theory of pseudodifferential operators *Hardy-type inequalities *linear and non-linear hyperbolic equations and systems *Schrödinger equations *water-wave equations *Euler-Poisson systems *Navier-Stokes equations *heat and parabolic equations Various levels of graduate students, along with researchers in PDEs and related fields, will find this book to be an excellent resource. Contributors T. Alazard                                P.I. Naumkin J.-M. Bony                              F. Nicola N. Burq                                   T. Nishitani C. Cazacu                                T. Okaji J.-Y. Chemin                           M. Paicu E. Cordero                              A. Parmeggiani R. Danchin                               V. Petkov I. Gallagher                              M. Reissig T. Gramchev                            L. Robbiano N. Hayashi                               L. Rodino J. Huang                                  M. Ruzhanky   D. Lannes                                J.-C. Saut F. Linares                                N. Visciglia P.B. Mucha                             P. Zhang C. Mullaert                              E. Zuazua T. Narazaki                             C. Zuily.